Rancang Bangun Smart Doorlock System Berbasis Arduino - Muhamad Adlan Ridhani; Suci Sri Utami Sutjipto (Jurnal Informatika Kesatuan, 2025)
Theft cases that are rampant in the flat area are a major problem in, flat security is an important point to prevent it. This research has the aim of making a design of a smart door lock system with various door opening methods based on the Arduino microcontroller. The Prototype method is used in this study to create a design of a smart door lock system that starts from the stages of requirements gathering, designs prototype, building prototypes, testing prototypes, and implementing them on a model. After completing all stages in building a smart door lock system, the conclusion obtained is that 3 locking methods are applied in the smart door lock system, namely rfid, keypad, and knock. The smart door lock system has 2 servos that act as locks on the door.   Keywords : Arduino, Smart Doorlock, Prototyping